The Existence and Global $p$-Exponential Stability of Periodic Solution for Stochastic BAM Neural Networks with Delays (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we consider a class of stochastic BAM neural networks with delays. By establishing new integral inequalities and using theproperties of spectral radius of nonnegative matrix, some sufficient conditionsfor the existence and global $p$-exponential stability of periodic solution forstochastic BAM neural networks with delays are given. An example is provided to show the effectiveness of the theoretical results.